Tri-band HIS backed spiral antenna for wireless LAN applications - Mohamad, Sarah Yasmin; Cahill, Robert; Fusco, Vincent (John Wiley, 2015)
This study reports the performance of an Archimedean spiral antenna, which exhibits unidirectional circularly polarized radiation patterns with a peak gain >8 dBic in the lower (2.4–2.485 GHz) and upper (5.15–5.35 and 5.725–5.875 GHz) Wireless local area network frequency bands. The required backlobe suppression and impedance match are obtained by placing a multiresonant high impedance surface (HIS) in close proximity to the radiating aperture. Simulated and measured radiation patterns are shown at the center frequency of all three channels and a comparison of the key performance metrics is made with free space and metal backed antenna arrangements to demonstrate the enhancements which are attributed to the HIS reflector.